ARABIC LEARNING AND RELIGIOUS CONVERSION - Abdul-Rahman Bahry (Epistemé: Jurnal Pengembangan Ilmu Keislaman, 2019)
The government of the State of Ohio has designed mandatory programs to help NRC’s female inmates to prepare themselves upon their release back to the community; one of the programs is Islamic education for Muslim prisoners. This program reserves as an opportunity for Muslim missionary (dai) for exercising dakwah (Islamic proselytization) activism, not only for Muslim prisoners, but also as a gate to introduce Islam to non-Muslim inmates. Particularly for the non-Muslim prisoners, they are interested in studying reading and writing Arabic as they are voluntarily joining the Arabic class. This article tries to over a new perspective on Islamic education and dakwah activism. Taking a close look at the lives of prisoners at the state prison of Ohio, this article mainly discusses the intermingled sphere of Islamic education for the Muslim and religious conversion. It further argues that teaching Arabic resorts as a gate for Muslim missionary to introduce Islam for non-Muslim prisoners who voluntarily participated in this language class and religious conversion to Islam often follows their participation. Thus, as the discussion of this article demonstrates, there has been a close connectivity between the ‘neutral’ language class with religious conversion.